C-reactive Protein in HPV-Positive and HPV-Negative Oropharyngeal Cancer. (March 2019) - Johnson-Obaseki, Stephanie; Caulley, Lisa; Corsten, Martin; Liu, Geoffrey; Dimitroulakos, Jim; Goldstein, David; Irish, Jonathan; Rider, Jennifer
Objective: Evaluate serum C-reactive protein (CRP) in human papillomavirus (HPV)–positive oropharynx cancer as compared with HPV-negative oropharynx cancer and determine if CRP levels were associated with overall survival and/or recurrence-free survival. Study Design: Prospective cohort study. Setting: Tertiary care academic cancer center between 2007 and 2010. Subjects and Methods: Among patients with oropharynx cancer and confirmed HPV status, plasma CRP levels were measured with a high-sensitivity ELISA kit. Multivariable logistic regression analysis compared 4 categories of CRP (low, moderate, high, very high) between the HPV-positive and HPV-negative groups. Kaplan-Meier methods and Cox regression models were used to determine overall survival and recurrence-free survival by CRP level in both populations. Results: Between 113 HPV-positive and 110 HPV-negative patients, CRP levels were significantly higher in the HPV-positive group, but these levels did not demonstrate a statistically significant dose-response trend. Higher CRP levels were also associated with reduced overall survival ( P = .016) and recurrence-free survival ( P < .001) within the HPV-negative group in univariable analysis; in multivariate analysis, the comparisons were not significantly different. Within HPV-positive oropharynx cancer, CRP levels were not significantly associated with overall survival or recurrence-free survival in univariable or multivariable analyses. Conclusion: Circulating CRP was higher in HPV-positive versus HPV-negative oropharynx cancer. Among HPV-negative patients, higher CRP levels were associated with reduced survival.